The Integration of Selober Traditional Music Within the song “Hakikat Sebuah Cinta” by Dr. Azam Dungun - Lalu Ahmad Alfian Bakti; Mohd Azam Sulong; Affendi Ramli (Universitas Hamzanwadi, 2024)
This study aims to explore the integration of traditional Lombok music, particularly the